Oncogenic KRAS Drives Metabolic Vulnerabilities by Directly Regulating Metabolic Enzymes in Cancer - Zhang, Liyi (Global Medical Genetics, 2020)
Metabolic reprogramming, such as enhanced aerobic glycolysis, allows cancer cells to maintain viability and promote proliferation. It is one of the major consequences of oncogenic mutations. KRAS is the most frequently mutated oncogene in human cancer. It is thought to be closely related to metabolic reprogramming. However, it is not clear whether it can participate in metabolic reprogramming by directly regulating metabolic enzymes. Additionally, the functional differences among the splice variants of KRAS have not been determined. In a study, recently published in Nature, Amendola et al reported a unique interaction between one of the KRAS splice variants (KRAS4A) and the major glycolytic enzyme (hexokinase 1) in cancer cells. Their findings indicated that a better understanding on the regulation of hexokinase 1 by KRAS may reveal novel therapeutic strategies.
Keywords: cancer metabolism; metabolic reprogramming; aerobic glycolysis; KRAS; KRAS4A hexokinase 1